2021
DOI: 10.1007/s00190-021-01586-6
|View full text |Cite
|
Sign up to set email alerts
|

Aliasing of ocean tides in satellite gravimetry: a two-step mechanism

Abstract: Ocean tide aliasing is one of the largest error sources in satellite gravimetry. Despite its importance, the aliasing mechanism of ocean tides in satellite gravimetry is only partially understood. This paper explains tidal aliasing as a two-step mechanism. The primary aliasing is caused by orbit undersampling of original tidal signals. The secondary aliasing is due to undersampling of the primary aliasing signals through gravity recovery in discrete time intervals. The two-step aliasing mechanism is demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In our study, we did not consider the impact of tides and did not eliminate the aspect of tidal aliasing, which is one of the largest source of error in satellite gravimetry (Liu and Sneeuw 2021) and would require a tidal model for the WTNA. On the other hand, a careful inspection of the tidal constituents of the M 2 , S 2 , N 2 , and K 2 tides (Beardsley et al 1995;Hart-Davis et al 2021) indicated strong tidal signals on the Amazon shelf where the water depth is < 20 m. This area is a relatively small part of the Amazon shelf and the small phase variation of tidal currents and surface elevation across the shelf suggest that the semi diurnal tide is a strongly damped standing wave (Geyer et al 1991), which might contribute to the meandering structure observed in the M174 SSS figures.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we did not consider the impact of tides and did not eliminate the aspect of tidal aliasing, which is one of the largest source of error in satellite gravimetry (Liu and Sneeuw 2021) and would require a tidal model for the WTNA. On the other hand, a careful inspection of the tidal constituents of the M 2 , S 2 , N 2 , and K 2 tides (Beardsley et al 1995;Hart-Davis et al 2021) indicated strong tidal signals on the Amazon shelf where the water depth is < 20 m. This area is a relatively small part of the Amazon shelf and the small phase variation of tidal currents and surface elevation across the shelf suggest that the semi diurnal tide is a strongly damped standing wave (Geyer et al 1991), which might contribute to the meandering structure observed in the M174 SSS figures.…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, a highfrequency signal will map into lower frequency due to the incomplete sampling and result in sampling a false signal with longer period. Aliasing in satellite gravimetry is induced by a more complicated two-step mechanism [6]. The primary aliasing is caused by orbit under-sampling of original high frequency signals and the secondary aliasing is due to under-sampling of the primary aliasing signals through gravity recovery in discrete (monthly) time intervals.…”
Section: Introductionmentioning
confidence: 99%
“…An a posteriori method for de-aliasing of OT errors in future double-pair missions was proposed by Liu et al (2016), also giving hints about optimal choices for orbit constellations to mitigate OT aliasing effects. Liu & Sneeuw (2021) describe OT aliasing as a two-step mechanism, with orbit sampling as the first step and gravity recovery as the second step. Another promising approach is the direct estimation of selected OT constituents.…”
mentioning
confidence: 99%